Biologi Ulat Grayak (Spodoptera frugiperda J. E Smith) - Desi Karlina; Samharinto Soedijo; Helda Orbani Rosa (JURNAL PROTEKSI TANAMAN TROPIKA, 2022)
Research on the life cycle and life balance of Spodoptera frugiperda (J. E Smith) has been conducted from September to November 2021 at the Entomology Laboratory of the Department of Pests and Plant Diseases ULM Banjarbaru. The results showed that S. frugiperda underwent changes from egg, larva, pupa and imago stages. This change is called complete metamorphosis. The average number of eggs produced is 45.14 eggs with an egg stage of 7 days, the larval stage has 6 instars, each time span (days) ranges from 2.4 to 3.4, the pupal stage is 7.5 days and the imago stage with brown wings. The male imago has a distinctive pattern while the female imago does not have a distinctive pattern. Imago male with a vulnerable time of 8 days while the female imago 9 days. From the life table, it is known that the GRR value is 316 individuals/generation, the R˳ value is 115.916 individuals/parent/generation, the T value is 30,197 days, the r value is 0.157 individuals/parent/day and the value is 1,170 individuals/parent/day.